جريمة اختطاف الأطفال و آليات مكافحتها في القانون الجزائري - بوصاق شعيب- مقورة لخضر (جامعة المسيلة, 2020)
تهدف الدراسة الى تبيان الانعكاسات الخطيرة لجريمة اختطاف الاطفال على المجتمع حيث أن الغرض من هذه الدراسة هو إزالة اللبس عن جريمة اختطاف الاطفال من خلال تحديد مفهومها وتمييزها عن باقي الجرائم الأخرى، كذلك من خلال الكشف عن الأسباب المساعدة في انتشارها، وعن السبل لمواجهة هذه الجريمة والسعي للحد منها ومكافحتها. نظرا لخطورتها فقد تناولتها المنظومات القانونية المختلفة بالتجريم، منها القانون العقوبات الجزائري، وبينت الجزاء العقابي لها، في إطار سياسة تجريم تهدف لمحاصرة الجريمة والحد منها، ووصلت في تشديد العقاب حد الحكم على الجناة بالسجن المؤبد، أو بالإعدام ، في حال ما اقترن الفعل بظرف تشديد كالقتل. المشرع الجزائري كغيره عاقب على هذه الجريمة بعقوبة جناية وجنحة، كما يعاقب على المحاولة أو الشروع فيها ودون أن ننسى أن المشرع الجزائري وضع أمام الجاني طريقة للعدول فأفاده بالأعذار المخففة و ربطها بشروط معينة. أن المتأمل للحوادث الإجرامية والملفات القضائية يجد أن ظاهرة الاختطاف تتصدر قوائم الممارسات الإجرامية الموجهة ضد الأطفال عموما. على المسؤولين خاصة الأمن والقضاء محاربتها والّتصدي لها، والضرب بيد قاسية على كل من يهدف إلى ترويع الأفراد وهذا تثبيتًا لدعائم الأمن في المجتمع. ويبقى القول بأنه عندما نريد حل مشكلة ما فعلينا البدء بحّلها من أساسها حّتى يتم القضاء عليها كليا . Research Summary The study aims to demonstrate the dangerous repercussions of the crime of child abduction on society, as the purpose of this study is to remove the confusion about the crime of child abduction by defining its concept and distinguishing it from other crimes, as well as by revealing the causes that help in its spread, and the ways to confront this crime and strive To reduce and combat them. Due to its seriousness, various legal systems have dealt with criminalization, including the Algerian Penal Code, and it has shown its punitive punishment, within the framework of a criminalization policy aimed at surrounding crime and limiting it, and has reached in the severity of punishment the level of sentencing the perpetrators to life imprisonment or death, if the act is accompanied by an aggravating circumstance Like killing. The Algerian legislator, like others, punishes this crime with a penalty of felony and misdemeanor, and also punishes attempting or attempting it, and without forgetting that the Algerian legislator has put in front of the perpetrator a method of rectification, so he informed him of mitigating excuses and linked them to certain conditions. A person who studies the criminal incidents and judicial files finds that the phenomenon of kidnapping tops the lists of criminal practices directed against children in general. Officials, especially security and the judiciary, must fight and confront them, and strike with a harsh hand everyone who aims to terrorize individuals, and this is to confirm the foundations of security in society. It remains to say that when we want to solve a problem, we must start solving it from the ground up until it is completely eliminated.
Keywords: اختطاف الأطفال -مكافحتها -القانون الجزائري